2019
DOI: 10.7717/peerj.6723
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the protein profile of silkworm (Bombyx mori) pupae reared on a well-calibrated artificial diet compared to mulberry leaf diet

Abstract: Background Silkworm pupae is the main by-product of the sericulture industry with an interesting nutritional profile, especially in terms of proteins. In consideration of its possible use as a food or food ingredient in Western countries, a comparative proteomic experiment has been performed to investigate the differences of the protein profile of male and female silkworm pupae reared on mulberry leaves or on an artificial diet. Methods The nutritional profile of lyophilized silkworm pupae in terms of dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
0
24
1
Order By: Relevance
“…Silkworms belong to the phylum Arthropoda, which includes crustaceans. A comparative proteomic study showed that some pupae proteins are differentially expressed when comparing gender and diet of silkworm larvae (Lamberti et al., 2019 ). Of note, the levels of known allergens in female silkworm pupae reared on mulberry leaves were lower compared to those reared under other experimental conditions (Lamberti et al., 2019 ).…”
Section: Silkworm Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…Silkworms belong to the phylum Arthropoda, which includes crustaceans. A comparative proteomic study showed that some pupae proteins are differentially expressed when comparing gender and diet of silkworm larvae (Lamberti et al., 2019 ). Of note, the levels of known allergens in female silkworm pupae reared on mulberry leaves were lower compared to those reared under other experimental conditions (Lamberti et al., 2019 ).…”
Section: Silkworm Allergymentioning
confidence: 99%
“…A comparative proteomic study showed that some pupae proteins are differentially expressed when comparing gender and diet of silkworm larvae (Lamberti et al., 2019 ). Of note, the levels of known allergens in female silkworm pupae reared on mulberry leaves were lower compared to those reared under other experimental conditions (Lamberti et al., 2019 ). Thus, the allergen profile of silkworm pupae could be associated with gender and diet and so could be regulated.…”
Section: Silkworm Allergymentioning
confidence: 99%
“…The LC‐MS/MS analyses were performed with a micro‐LC system from Eksigent Technologies (Dublin, CA, USA) coupled with a 5600+ Triple TOF TM system (AB Sciex, Concord, Canada) equipped with a Duo Spray TM Ion Source and a CDS (Calibrant Delivery System). The run conditions were set as described in Lamberti et al (). The mass spectrometer worked in data‐dependent acquisition mode (DDA) (Cvijetic et al ).…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Silkworms (Bombyx mori) convert plant proteins into silk and use it as a source of food, with a rich nutritional profile, especially in terms of proteins, fat, and chitin contents. 12 Silkworm pupae has been used as a medicine and as an animal feed in many Asian countries for a long time. 19 Silkworm pupae has a high reproduction rate, short life period and short space requirements which provides a practicable alternative opportunity for food safety such as scombroid poisoning.…”
Section: The Level Of Bacteria Colonymentioning
confidence: 99%
“…They are a low cost healthy food source of high nutritional value including protein, lipids and essential amino acid. 11,12 High levels of histamine in food is known to cause food poisoning but it does not alter the organoleptic quality, leading to histamine-contaminated foods being viewed as normal. Therefore, scombroid poisoning is frequently misdiagnosed.…”
mentioning
confidence: 99%